Fallout observations in India after the First French Atomic Test in Sahara - VOHRA, K. G.; BRATNAGAR , V. S.; RANGARAJAN, A. (MAUSAM, 1961)
The data on the airborne radioactive fallout and surface deposition of fallout in India after the French Atomic Test in Sahara on 13 February 1960, are reported. The increase in activity was observed during the period 16 February to 20 March. The maximum level of deposition at Bombay was about 170 millicuries per square kilometre, deposited between 17 and 18 February. This level was observed in the absence of rainfall. The air concentrations of fallout showed large fluctuations, with a maximum level of about 12 micro microcuries per cubic metre of air at Bombay between 19 and 20 February. Meteorological interpretations of the data a presented and estimates of total radiation dose from fallout from this test are carried out.